S-Adenosyl-L-Homocysteine Hydrolase Inhibition by a Synthetic Nicotinamide Cofactor Biomimetic - Kailing, Lyn L.; Bertinetti, Daniela; Paul, Caroline E.; Manszewski, Tomasz; Jaskolski, Mariusz; Herberg, Friedrich W.; Pavlidis, Ioannis V. (Frontiers in Microbiology, 2018)
S-adenosyl-L-homocysteine (SAH) hydrolases (SAHases) are involved in the regulation of methylation reactions in many organisms and are thus crucial for numerous cellular functions. Consequently, their dysregulation is associated with severe health problems. The SAHase-catalyzed reaction is reversible and both directions depend on the redox activity of nicotinamide adenine dinucleotide (NAD+) as a cofactor. Therefore, nicotinamide cofactor biomimetics (NCB) are a promising tool to modulate SAHase activity. In the present in vitro study, we investigated ten synthetic truncated NAD+ analogues against SAHase from the root-nodulating bacterium Bradyrhizobium elkanii (BeSAHase). Among this set of analogues, one was identified to inhibit the SAHase in both directions. Isothermal titration calorimetry (ITC) and crystallography experiments suggest that the inhibitory effect is not mediated by a direct interaction with the protein. Neither the apo-enzyme (i.e., deprived of the natural cofactor), nor the holo-enzyme (i.e., in the NAD+-bound state) were found to bind the inhibitor. Yet, enzyme kinetics point to a non-competitive inhibition mechanism, where the inhibitor acts on both, the enzyme and enzyme-SAH complex. Based on our experimental results, we hypothesize that the NCB inhibits the enzyme via oxidation of the enzyme-bound NADH, which may be accessible through an open molecular gate, leaving the enzyme stalled in a configuration with oxidized cofactor, where the reaction intermediate can be neither converted nor released. Since the reaction mechanism of SAHase is quite uncommon, this kind of inhibition could be a viable pharmacological route, with a low risk of off-target effects. The NCB presented in this work could be used as a template for the development of more potent SAHase inhibitors.